Access denied? Twenty-first-century technology in schools - Male, Trevor; Burden, Kevin (Technology, Pedagogy and Education, 2014)
This article considers how developments in technologies have transformed the kind of social interaction possible over the Internet, making it feasible to undertake discourse and dialogue without having to rely solely on text-based mediation. This represents a fundamental change to learning, shifting from passive acquisition of someone else’s ideas to active learning experiences that empower people to inquire, critique, create, collaborate, problem-solve and create understanding. Such technologies are also about the portability of mobile digital devices which now have the potential to allow any-time access for users either through Wi-Fi or mobile broadband providers and for those devices to become personal. The implications for education are enormous and the anticipated change probably ranks alongside the introduction of the printing press in terms of historical importance. This article considers those implications and draws on research recently conducted in schools and other educational settings in the United Kingdom. The authors conclude that the need to allow use of personal digital devices in schools seems inexorable, the further we go into the new millennium. This simple premise is fraught with many difficulties and challenges, however, which suggest that for many students the current situation is ‘Access denied’.
Keywords: digital technology; learning; pedagogy